DEVELOPMENT OF KKNI-BASED TEACHING MODULES ON PETTY CASH MANAGEMENT MATERIAL - NANIK SRI HARYATI; Nina Oktarina, Nina Oktarina; Agung Kuswantoro, Agung Kuswantoro (Journal of Economic Education, 2025)
The purpose of this research to knowing the teaching modules that have been applied so far on the material, developing teaching modules, and producing the feasibility of teaching modules based on KKNI on the material of Petty Cash Management for class XI MPLB at SMK Asta Mitra Purwodadi. This study employs a quantitative approach and a research and development (R&D) method using the 4-D development model. The results of this study indicate that the previously used teaching module still contains several components that have not yet been integrated with KKNI and do not fully cover the competency aspects of students' skills. The material expert validation of the developed teaching module was deemed feasible with a score of 3.25. The media expert validation of the KKNI-based teaching module resulted in a score of 3.60. The Pearson correlation validity test yielded a score of 0.349, indicating validity. The reliability test of the questionnaire instrument for students' responses to the KKNI-based teaching module showed a Cronbach's alpha value of 0.950. The t-test result showed a significance value of 0.000, indicating a significant difference in skill competency improvement between the control and experimental classes, meaning that the developed KKNI-based teaching module is effective. The N-Gain score for improving students' skill competency in the experimental class was 0.76. Development of a KKNI-based teaching module to increase participant skill competency Because it teaches contextual materials so that participants get draft petty cash management and examples studies related cases​ direct to live in the industrial world.